Role of Innovation in the Development of a Country Economy - Simran K. Kahai; Tejinder Sara; Faye Hall Jackson (Business, Management and Economics: Research Progress Vol. 4, 2024)
The long-term economic growth and prosperity of a country are often linked to competitive technology and innovation. A nation’s higher-order competitive advantage can be built only with innovation. A firm must use technical innovation to develop cutting-edge products and processes that can bring success to it and the country. Michael Porter’s research on the broad question of how an economy progresses has received a great deal of attention. This paper discusses the role that innovation plays in global competition and provides examples showing how firms from selected emerging markets use innovation to compete with global firms from the developed world. This paper also discusses the role of innovative capability in the growth of a country. In this context, an empirical model was used to identify the determinants of the innovative capability of a country. Data from 121 countries were analyzed based on eight variables discussed in the previous section – institutions, business sophistication, government size, training and education, technological readiness, market size, labor market efficiency, and infrastructure. Based on the results of the empirical analysis, it can be concluded that the innovative capability of a country is most significantly affected by the quality of three variables - business networks and supporting industries (business sophistication) in the country, the flexibility given to the country’s firms to recruit and allocate workers to the most productive tasks (labor market efficiency), and the quality of a country’s public institutions within which the economy’s main players interact (institutions). The discussion of these determinants should be useful to policymakers in countries attempting to promote economic growth by improving the productivity of firms in their respective countries. The policy focus should be on developing rules and regulations for improvement in the quality of public institutions, quality of business networks and supporting industries, and flexibility in the labor markets in their countries should be stressed.